Prominenten van de beeldende kunst in de twintigste eeuw 1901-2000 - Van Wiemeersch, Albert; Van Wiemeersch, Albert (Tielt : Lannoo, 2003)
Abakanowicz, Magdalena ; Abramovic, Marina ; Acconci, Vito ; Ackermann, Franz ; Adam, Henri-Georges ; Adami, Valerio ; Adams, Dennis ; Adams, Robert ; Aeppli, Eva ; Aeschbacher, Hans ; Afro ; Agam, Yaacov ; Ahtila, Eija-Liisa ; Aillaud, Gilles ; Akkerman, Ben ; Akkerman, Philip ; Alberola, Jean-Michel ; Albers, Josef ; Albert, Jos ; Albright, Ivan Le Lorraine ; Alcopley ; Alechinsky, Pierre ; Alfaro, Andreu ; Alkema, Wobbe ; Alma, Peter ; Aloïse ; Alt, Otmar ; Altenbourg, Gerhard ; van Amen, Woody ; Van Anderlecht, Englebert ; Andre, Carl ; de Andrea, John ; Andrea, Pat ; Andrews, Michael ; Andriesse, Erik ; Andriessen, Mari ; Anselmo, Giovanni ; Antes, Horst ; Anthoons, Willy ; Anuszkiewicz, Richard ; Anzinger, Siegfried ; Appel, Karel ; Applebroog, Ida ; Arakawa, Shusaku ; Archipenko, Aleksandr ; Arden, Quin ; Ardon, Mordechai ; Arikha, Avigdor ; Armajani, Siah ; Arman ; Armando ; Armitage, Kenneth ; Armleder, John ; Arnould, Marcel ; Arp, Hans (Jean) ; Arroyo, Eduardo ; Art & Language ; Artschwager, Richard ; Asher, Michael ; Asmus, Dieter ; Asselbergs, Gustave ; Atelier van Lieshout ; Atlan, Jean-Michel ; Attersee, Christian Ludwig ; Aubroeck, Karel ; Auerbach, Frank ; Avati, Mario ; Avery, Milton ; Aycock, Alice ; Ayrton, Michael ; Baader, Johannes ; Bacon, Francis ; Baer, Jo ; Baertling, Olle ; Bailleux, Cesar ; Baj, Enrico ; van Bakel, Gerrit ; Bakker, Jits ; Baldessari, John ; Baljeu, Joost ; Balka, Miroslaw ; Balkenhol, Stephan ; Balla, Giacomo ; Balle, Mogens ; Balthus ; Banana, Anna ; Bandau, Joachim ; Barcelo, Miquel ; Barlach, Ernst ; Baroni, Vittore ; Barré, Martin ; Barry, Robert ; Bartlett, Jennifer ; Baselitz, Georg ; Baskin, Leonard ; Basquiat, Jean-Michel ; Bauchant, André ; Baugniet, Marcel-Louis ; Baumeister, Willi ; Baumgarten, Lothar ; etc.
volwassenen
boek